“Non-Triangle Plane” Surgical Technique of Video-Assisted Thoracic Surgery Atypical Segmentectomy for Stage IA Non-Small-Cell Lung Cancer: Early Experience - Zhou, Chao; Qian, Jun; Li, Wentao (Frontiers in Surgery, 2021)
Objectives: To evaluate the safety and feasibility of a novel surgical technique (“non-triangle plane” technique) of two-port (mini-utility) video-assisted thoracic surgery (VATS) atypical segmentectomy (S3+S1+2C) with tunneling stapler for small-sized non-small-cell lung cancers (NSCLCs) located in left S3 close to the intersegmental plane between S3 and S1+2C. Materials and Methods: This retrospective descriptive study included sixteen patients who, between April 2016 and December 2019, underwent a single two-port (mini-utility) VATS atypical segmentectomy (S3+S1+2C) with tunneling stapler technique for small-sized NSCLCs with a GGO rate of more than 50% by a constant surgical team in two hospitals. Perioperative data and survival data were collected and retrospectively analyzed. Postoperative follow-up was performed every six months. Results: Six patients were with adenocarcinoma in situ, and ten with minimally invasive adenocarcinoma. The mean surgical margin was 14.06±3.02 mm. The mean operation time was 53.88±9.76 minutes. The mean duration of chest tube drainage was 4±1.21 days, and the median length of postoperative hospital stay was four days. There was no perioperative morbidity and mortality. The median follow-up was 47.5 months (17-61 months). No recurrences occurred, and all patients were still alive at the last registered follow-up (May 31, 2021). Conclusion: Two-port (mini-utility) VATS atypical segmentectomy (S3+S1+2C) with tunneling stapler technique is a safe and feasible option for the treatment of small-sized NSCLCs located in left S3 close to the intersegmental plane between S3 and S1+2C.